Dybdeøkologi og kosmisk livserotik - Introduktion til Ludwig Klages’ ”Menneske og jord” - Ylander, Lars (Slagmark - Tidsskrift for idéhistorie, 2018)
Ludwig Klages’ famous essay from 1913 is here translated into Danish for the first time. According to Klages, the planet-wide destruction of nature is a disastrous outcome of a runaway mad civilisation focused on progress. Famously, he finds the root of the madness to be an intricate entanglement of science, technology, capitalism and Christianity. Ultimately, these are all aspects of what he calls Spirit (Geist) – an alienating and life-disruptive power that tears man away from its original being interwoven with living nature. Its benign adversary, Soul, is characterised by caring for life. This elementary or cosmic love is linked to Soul’s way of recognizing reality through a dynamical flow of sensual pictures. On the other hand, Spirit’s drive to destroy and kill is related to its way of fixating knowledge of the world by means of concepts. Klages diagnoses modern ‘civilisation’ as an era of downfall of the Soul. The devastating events the following summer of 1914 may be seen as a consequence of the bad cultural standing. An anthropological ecology, spirit-dominated and with civilised man’s interest as its core value, is not enough to save nature. Only a deep ecology, where Soul dominates Spirit, can do so, moving the value focus away from man to Earth.